The Politics of Property: Place-Making in Una, Saxon, and Arcadia - Sarah Buckmaster (The Journal for Undergraduate Ethnography)
Una, Saxon, and Arcadia are three neighborhoods in Spartanburg County, South Carolina undergoing an era of neighborhood re- organization, change, and development. As historic textile mill villages from the county’s age of industrialization, the Una, Saxon, and Arcadia neighborhoods today are characterized by privately-owned, mid-century mill homes and a high population of renters. Neighbors are concerned about the dilapidated housing stock falling into disrepair and the resulting impacts of abandoned and condemned properties. To advocate alongside Una, Saxon, and Arcadia residents for equitable neighborhood investment, our research team conducted two years of mixed-method ethnographic research across the three neighborhoods to determine the impacts of abandoned and condemned properties on neighborhood wellness. Through our research collaborations, our team identified deeply personal and political associations between residents, their homes, and their stake in the Una, Saxon, and Arcadia community. Advocating for equity in Una, Saxon, and Arcadia cannot be simplified to one policy recommendation or development plan. Rather, collective organization and engagement amongst residents bolstered by key stakeholders, such as the county, may provide an equitable and inclusive path to reimagining neighborhood futures.